The Role of Hemp (Cannabis sativa L.) as a Functional Food in Vegetarian Nutrition - Gianluca Rizzo; Maximilian Andreas Storz; Gioacchino Calapai (Foods, 2023)
Recently, there has been a renewed interest in Cannabis sativa and its uses. The recreational use of inflorescences as a source of THC has led to the legal restriction of C. sativa cultivation to limit the detrimental effects of psychotropic substance abuse on health. However, this has also limited the cultivation of textile/industrial varieties with a low content of THC used for textile and nutritional purposes. While previously the bans had significantly penalized the cultivation of C. sativa, today many countries discriminate between recreational use (marijuana) and industrial and food use (hemp). The stalks of industrial hemp (low in psychotropic substances) have been used extensively for textile purposes while the seeds are nutritionally versatile. From hemp seeds, it is possible to obtain flours applicable in the bakery sector, oils rich in essential fatty acids, proteins with a high biological value and derivatives for fortification, supplementation and nutraceutical purposes. Hemp seed properties seem relevant for vegetarian diets, due to their high nutritional value and underestimated employment in the food sector. Hemp seed and their derivatives are a valuable source of protein, essential fatty acids and minerals that could provide additional benefit to vegetarian nutrition. This document aims to explore the information available in the literature about hemp seeds from a nutritional point of view, highlighting possible beneficial effects for humans with particular attention to vegetarian nutrition as a supplemental option for a well-planned diet.